La scienza delle droghe - Samorini, Giorgio (Cultura y Droga, 2003)
Abstract: With regards to the social perplexity that exists about the use of the term drugs, especially the difference between the drugs problem and the drugs phenomenon, the proposal by Paolo Mantegazza (1831–1910) has been adopted again, he was an Italian researcher who talked about the necessity to create the field of scientific research called The Science of Drugs, as a specific discipline about this topic. Such perplexity has limited the scientific possibilities about the use of drugs concerning the positive knowledge for human beings. He illustrates about this matter based on the article by the Russian writer Leon Tostoi called. Why do people use drugs? In which he argues about the perplexity of establishing a direct causality in the drug of such behaviors rather than specific situations going on in society. He stresses the relationship between biology and natural behaviors in animals that use drugs, and for the human case, the reference to the context of human nature and culture.